Biological control of Rhizoctonia solani by Trichoderma spp. and by fluorescent Pseudomonas spp in tomato (Lycopersicon esculentum L.) - Porfirio-Silva, Zenaldo; Homechin, Martin (Semina: Ciências Agrárias, 1993)
<!–[if gte mso 9]> Normal 0 21 MicrosoftInternetExplorer4 <![endif]–> <!– /* Font Definitions */ @font-face font-family:Verdana; panose-1:2 11 6 4 3 5 4 4 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:536871559 0 0 0 415 0; /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; @page Section1 size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:35.4pt; mso-footer-margin:35.4pt; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–> The biological control of Rhizoctonia solani by the use of Trichoderma harzianum and Pseudomonas fluoresceâ„¢ was studied in laboratory and greenhouse conditions. Tomato seeds (Lycopersicon esculentum L., cv. AGROCICA 33), were inoculated by dipping them in an inoculum suspension of isolates of Pseudomonas spp. (1x108 ufc/mlj and Trichoderma spp. (2 x 106 spores/ml). These seeds were sown unsterilized soil previously (72 h) inoculated with an isolate of R. solani RS-25. The pathogen inoculum, R. solani RS-25 growth obtained in sunflower seeds was utilized. During 30 days from sowing, seedling emergence and development, dumping-off incidence and R. solani pathogenicity degree were evaluated. At 10 days, the emergence rate in the control treatment was of 58,44%, while the treatment with the antagonistic organisms increased seedling emergence, as well as decreased to the damping-off incidence in 12.15% to 68,81% as compared to the inoculated check.